Pelatihan Peningkatan Keterampilan Sosial Emosional Bagi Pendidik dan Tenaga Kependidikan - Fitriana, Siti; Suhendri, Suhendri; Setiawan, Agus; Prasetyo, Agung (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
In the implementation of the Independent Curriculum, teachers are required to be closer and understand students in depth, this is because learning focuses on the needs of students. Through differentiated learning, teachers are expected to have good social-emotional skills (KSE), not only when teaching but also when interacting outside the classroom. This also applies to education staff, who are expected to be able to show empathy, manage emotions, and build positive relationships. Thus, in the educational process not only develops academic abilities but also students' social and emotional skills (KSE), which include; emotional management, empathy, and the ability to collaborate, which are important for the future success of students. Unfortunately, there are still many challenges in school, such as a lack of ability to recognize emotions, establish healthy relationships, and make wise decisions. Therefore, KSE training for educators and education personnel is important. With the methods of discussion, lectures, questions and answers, and brainstorming, this training aims to improve the understanding and skills of educators and education staff. As a result, there is an increase in teachers' perception of understanding and social-emotional skills, which is characterized by educators being able to develop ideas in order to be inspirational role models and develop ideas in creating an environment that supports positive development, as well as building the future of students by always implementing social-emotional skills.